THE CORRELATION BETWEEN MOTIVATION AND LEARNING OUTCOMES IN ENGLISH CLASS: Hubungan Motivasi Dan Hasil Belajar Di Kelas Bahasa Inggris - Zahrina (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2020)
Many factors can affect student’smotivation to learn. They can be found from internal and external factors. Learning without support will not work effectively, the result probably disappointed or the worst effect– failed. The complex issues rise and influence teaching and learning that make educators and other person related in this case to think and consider. The problem such individual differences where students come with various background, ability and motivation demand teacher to skillfully handle the situation.Sometimes, when such the problem above cannot be solved and seriously troubles teaching-learning process, it will ruin everything, particularly the goal of teaching learning itself.